AN ANALYSIS OF AUTONOMOUS LEARNING STRATEGIES USED BY SENIOR HIGH SCHOOL STUDENTS - Kemala, Zia (2014)
This study investigated the characteristics of autonomous learners, autonomous learning strategies which were applied by them, and the factors influencing the autonomous learners in learning English. This study was conducted in second grade of one senior high school in Bandung. This study employed a qualitative case study. Case study was deemed to be relevant for this study since it deals with specific phenomenon of autonomous learner as a single case which was analyzed and described. The data were obtained from the students which were collected through observation, questionnaire, and interview. After collecting the data, it was analyzed inductively based on qualitative data analysis and interpreted to answer the research questions. The study revealed three findings related to the research questions. First, it was found that all of the autonomous learners were able to identify their learning needs, find the materials that they intended to learn, and select learning projects, there were ten learners who worked collaboratively to learn English and used the teacher as a guide in learning English, nine learners learned outside the class, eight learners set their goals to learn English, six learners assist themselves in problems to tackle and chose when and where they will learn, three of them who plan activities to learn English and only a learner who decided when learning was complete. Second, the autonomous learners employedfour strategies which were (1) memory strategy, (2) social strategy, (3) cognitive strategy and (4) metacognitive strategy. Memory and social strategy were the most preferred learning style among autonomous learners. Third, autonomous learners were influenced by five factors which are (1) motivation, (2) social environment, (3) task, (4) teacher and (5) material. These finding suggest that the teacher must encourage and promote students to become autonomous learner because students will get more benefit from becoming autonomous learners.